Perlindungan dan Pengakuan Masyarakat Adat dan Tantangannya dalam Hukum Indonesia - Jawahir Thontowi (Jurnal Hukum IUS QUIA IUSTUM, 2013)
The research discusses: First, the existence of traditional law community and its regulation in Constitution 1945; second, the attempts that the traditional law community (MHA) must do as to preserve their values in a community; third, the relevance between theory and concept in preparing the development and making of the legal instrument for MHA values conservation. The literature study was conducted by collecting the primary and secondary materials to answer the research questions. The findings conclude that: First, the MHA position has been ratified as stipulated in Article 18B verse (2) and Article 28 verse (3) of Constitution 1945 and in other sectoral laws. Second, the MHA status and other traditional rights are not yet able to apply due to internal factors including the contradiction between the regulations of law related to MHA regulation and external factor, which is state institutions such as Ministry of Forestry and Ministry of Mining with formal evidence can easily turn down the MHA claim and its traditional rights. Third, the strengthening of MHA status and its traditional rights will increase if the Central Government describes them in the more concrete law.Key words : Conservation, MHA, constitutional rights